Hak Milik Atas Tanah Perspektif Imam al-Syafi’i dan Imam Ahmad bin Hanbal - Majid, Anugrah; Wijaya, Abdi (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
This article aims to describe and analyze related to land ownership rights, viewed from the perspective of Islamic law from the point of view of Imam Syafi’i and Imam Hambali which is then related to what happened in Ex. Bara-barayya, Kec. Makassar, Makassar City. In answering the problems above, the author uses a type of research that is classified as qualitative with the research approaches used are: theological-normative, pedagogical, psychological, and sociological. The sources of data for this research are local residents of Bara-barayya and community leaders. Furthermore, the data collection methods used were observation, interviews, documentation, and reference tracing. Then, data processing and analysis techniques were carried out through three stages, namely: data reduction, data presentation, and drawing conclusions. The results of this study indicate the history of the birth of land disputes in the Bara-barayya Village, Makassar District, Makassar City and also discuss the process of resolving land disputes, with this thesis it is hoped that this thesis can be a contribution to people who want to know more details about the history of disputes and the existing dispute resolution process. in Bara-barayya Village, Makassar District, Makassar City.